Problem Condition and Needs for Patient Triage at the Emergency Department in the New Normal Age, Tertiary Care Center, Health Region 2 - Chanuwat, Supaporn; Ruetrakul, Jirarat; Chairat, Rongnapa (NU Journal of Nursing and Health Sciences, 2025)
The purpose of this qualitative research was to study problem condition and needs of Triage at the emergency department of a tertiary care center in Health Region 2. Informer 12 professional nurses who had ability to triage patients and worked in the emergency department for at least 6 months. The in-depth interview was used for data gathering.Data were analyzed by descriptive and content analysis.The research found problems in 4 areas divided into 9 issues as follows. 1. Area of patients and information givers had 2 issues 1) complexity of the symptoms and signs of patients 2) readiness of relatives or caregivers to provide information. 2. Area of the screeners had 3 issues 1) lack of triage nurses during late night shifts 2) lack of additional support team and 3) insufficient competency of triage nurses 3. Area of screening tools and information technology had 2 issues 1) complexity to use the screening tools 2) complexity of technology usage 4. Area of location and equipment had 2 issues 1) unclear of access and room signs 2) inadequate equipment at certain times.The research found that the needs for patient triage in the Emergency Department consisted of 3 areas divided into 7 issues as follows. 1. Area of screener had 3 issues 1) regularly increase nurses’ patient triage competency 2) increase the number of nurses appropriate for each shift 3) increase support team according to work demand. 2. Area of tool and technology had the demand to ease data entry both in data complexity and data entry process. 3. Area of triage had 3 issues 1) specific place for triage which is convenient for access 2) appropriate furniture and equipment for triage 3) proper and clear signs for patients and relatives.